Upaya Peningkatan Hasil Belajar Peserta Didik dengan Model Pembelajaran Project Based Learning (PjBL) Pada Pata Pelajaran Usaha dan Energi alternatif Kelas X di SMAN 1 Magetan Tahun Pelajaran 2022/2023 - Yulia Amanati, Anis; Endang Purwaningsih; Dwikoranto; Munasir (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
ABSTRACT This study aims to improve the learning outcomes of cognitive, affective, and psychomotor physics in class X SMA Negeri 1 Magetan by using the Project Based Learning (PjBL) learning model. This study used the classroom action research (PTK) method which was carried out in collaboration between researchers, tutor teachers, and field assistant lecturers. Research procedures carried out in 2 cycles each in 4 stages, namely: Planning (Planning), Action (Action), Observation (Observation), and Reflection (Reflection). The results of this study are that the use of the PjBL learning model on the subject matter of work and energy can improve the learning outcomes of cognitive, affective, and psychomotor physics for class X students of SMA Negeri 1 Magetan. Cycle I had an average pretest score of 65.2 and an average posttest of 86.3, increasing in cycle II the highest posttest score achieved, namely an average pretest of 67.3 and an average posttest of 88.5. While the difference between the posttest and pretest average scores in cycle I was 21.1 points and cycle II was 21.2 points. This shows that there is an increase in physics learning outcomes from the three cognitive, affective and psychomotor aspects of students from cycle I to cycle II. Keywords: Learning Outcomes, Cognitive, Affective, Psychomotor, Classroom Action Research, Project Based Learning (PjBL)